PENERAPAN KONSEP BIOMEKANIKA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN SISTEM GERAK MANUSIA DI JENJANG SEKOLAH DASAR - Alimathus Sa’diyah; Mintohari; Selviari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The concept of biomechanics is one effort that can be used by teachers to teach students related learning related to biology and mechanics. Biomechanics is an interdisciplinary field that applies the principles of physics to biological systems to understand how organisms move and interact with their environment. The aim of this research is to determine the application of biomechanical concepts in human movement systems to improve student learning outcomes at elementary school level. The research carried out is included in the PTK (Classroom Action Research) type. This research was carried out in one of the elementary schools in Surabaya with a total of 25 students. The instruments used in this research consisted of student and teacher observation sheets, student activity sheets during the cycle, learning implementation sheets, and pretest posttest sheets. The results of this research are that this is shown in the learning outcomes obtained by students with many showing improvement and achievement of existing criteria.